In-situ synthesis of Ni–Co–S nanoparticles embedded in novel carbon bowknots and flowers with pseudocapacitance-boosted lithium ion storage. (12th February 2019) - Yang, Tao; Yang, Dexin; Mao, Qinan; Liu, Yangai; Bao, Liang; Chen, Yifan; Xiong, Qinqin; Ji, Zhenguo; Ling, Chris D; Liu, Hao; Wang, Guoxiu; Zheng, Rongkun
Abstract: We design a facile approach to prepare a bimetallic transition-metal-sulphide-based 3D hierarchically-ordered porous electrode based on bimetallic metal-organic frameworks (Ni–Co–MOFs) by using confinement growth and in-situ sulphurisation techniques. In the novel resulting architectures, Ni–Co–S nanoparticles are confined in bowknot-like and flower-like carbon networks and are mechanically isolated but electronically well-connected, where the carbon networks with a honeycomb-like feature facilitate electron transfer with uninterrupted conductive channels from all sides. Moreover, these hierarchically-ordered porous structures together with internal voids can accommodate the volume expansion of the embedded Ni–Co–S nanoparticles. The pseudocapacitive behaviours displayed in the NCS@CBs and NCS@CFs occupied a significant portion in the redox processes. Because of these merits, both the as-built bowknot and flower networks show excellent electrochemical properties for lithium storage with superior rate capability and robust cycling stability (994 mAh g −1 for NCS@CBs and 888 mAh g −1 for NCS@CFs after 200 cycles). This unique 3D hierarchically-ordered structural design is believed to hold great potential applications in propagable preparation of carbon networks teamed up with sulphide nanocrystals for high energy storage.